2019
DOI: 10.1007/s00214-019-2494-2
|View full text |Cite
|
Sign up to set email alerts
|

DFT study of two-photon absorption of octupolar molecules

Abstract: The two-photon absorption (TPA) properties of octupolar molecules based on a triphenyl-isocyanurate cyclotrimer, a 1,3,5-triphenyl-benzene or a triphenyl-triazine core were theoretically investigated using DFT and TD-DFT computations. These compounds are very promising regarding their potential application especially for optical limitation. These systems, which exhibit a three-fold axis, contain three arms with a terminal electron donating group linked in 1, 3 and 5 positions to the central C 3 N 3 O 3 isocyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
3
7
0
Order By: Relevance
“…In line with our previous studies [53,59], the simulations of 2PA spectra were also carried out for selected compounds using the damped cubic response theory of Jensen et al [60]. The calculations were performed using the SAOP functional, for sake of consistency with previous computations already reported on these compounds (see computational details in Section 4.5) [53]. The simulated 2PA spectra (ESI, Figure S17) revealed a first 2PA band for these compounds at lower energy than that experimentally determined with significantly higher 2PA cross-section values (Table 2).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In line with our previous studies [53,59], the simulations of 2PA spectra were also carried out for selected compounds using the damped cubic response theory of Jensen et al [60]. The calculations were performed using the SAOP functional, for sake of consistency with previous computations already reported on these compounds (see computational details in Section 4.5) [53]. The simulated 2PA spectra (ESI, Figure S17) revealed a first 2PA band for these compounds at lower energy than that experimentally determined with significantly higher 2PA cross-section values (Table 2).…”
Section: Discussionsupporting
confidence: 93%
“…The simulated 2PA spectra (ESI, Figure S17) revealed a first 2PA band for these compounds at lower energy than that experimentally determined with significantly higher 2PA cross-section values (Table 2). While an overestimation of the real 2PA cross-sections by this method was expected [53], the experimental trends were generally qualitatively fairly well reproduced within a given family of compounds [59]. Based on these SAOP calculations, we speculate that the cross-section of the first 2PA band of 3-CN or 3-NO 2 , which could not be experimentally determined, should be lower than that of the other 3-X compounds.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…56 In previous studies, we showed that SAOP/DZP calculations lead to TPA cross-sections that were in satisfying agreement with the experimental measurements. 57,58 The excited state lifetime was included in the theory using a damping parameter of 0.0034 atomic unit (a.u.) (B0.1 eV or B800 cm À1 ), 59 which was previously found to be suitable for TPA computations.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Such a large deviation between the measured and SAOP/DZP computed TPA cross-sections is generally expected and has been discussed in the literature. 57,58 Indeed, the main reason is that SAOP calculations (i) underestimate the HOMO-LUMO gaps and (ii) neglect solvent effects. Nevertheless, the theoretical results respect the trend experimentally observed for OMe-PV, NH 2 -PV, NPh 2 -PV and NBu 2 -PV.…”
Section: Two-photon Absorptionmentioning
confidence: 99%